(untitled) (Rudarsko-geološko-naftni zbornik, 2022)
The freezing technique has been employed for a long time to strengthen the mechanical properties of intact rock and rock mass; however, it has not received as much attention as it deserves. This paper thoroughly reviews the effect of freezing on the essential mechanical properties, including uniaxial compressive strength, tensile strength, and Young’s modulus. The laboratory tests include the determination of density, ultrasound speed propagation, and strength parameters such as uniaxial compressive strength, tensile strength, and Young’s modulus. According to previously published results, the strength of different rocks such as marl, limestone, sandstone, tuff, granite, and marble increased significantly due to freezing when the samples were tested in frozen conditions. However, there is variation in strength increase based on rock type. It is outlined here that freezing increases rock strength by a factor of 4 in porous rock and by a factor of 1.8 in crystalline rock. Additionally, Young’s modulus increases with a decrease in temperature; however, a further decrease in temperature from -10 to -20 °C has no effect on Young’s modulus. Moreover, mathematical modelling for frozen rock has been reviewed comprehensively. It was found that porosity, the density of rock grains, density of water, residual unfrozen water content, minimum unfrozen water content at freezing point, material parameters, the initial temperature of rock, crystal size, orientation and alignment of minerals, and the loading rate are the most critical parameters that influence frozen rock strength.